Internet of medical things paradigm of wearable devices - Cardona, Manuel; Solanki, Vijender Kumar 1980-; Cena, Cecilia E. García (CRC Press, Taylor & Francis Group, 2021)
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Preface -- Editors -- Contributors -- Chapter 1: Fundamentals and Paradigms in the Internet of Things -- Chapter 2: Internet of Medical Things: Current and Future Trends -- Chapter 3: An Overview on Wearable Devices for Medical Applications -- Chapter 4: Blockchain-Based IoT for Personalized Pharmaceuticals -- Chapter 5: Wearable/Implantable Devices for Monitoring Systems -- Chapter 6: Wearable Sensors for Monitoring Exercise and Fatigue Estimation in Rehabilitation -- Chapter 7: Conversational Agents for Healthcare Delivery: Potential Solutions to the Challenges of the Pandemic -- Chapter 8: Role of Big Data in e-Healthcare Application for Managing a Large Amount of Data -- Index
Description based on publisher supplied metadata and other sources
Keywords: Electronic books